Compartment Syndrome as a Result of Systemic Capillary Leak Syndrome. (5th September 2016) - Kyeremanteng, Kwadwo; D'Egidio, Gianni; Wan, Cynthia; Baxter, Alan; Rosenberg, Hans
Abstract : Objective . To describe a single case of Systemic Capillary Leak Syndrome (SCLS) with a rare complication of compartment syndrome. Patient . Our patient is a 57-year-old male, referred to our hospital due to polycythemia (hemoglobin (Hgb) of 220 g/L), hypotension, acute renal failure, and bilateral calf pain. Measurements and Main Results . The patient required bilateral forearm, thigh, and calf fasciotomies during his ICU stay and continuous renal replacement therapy was instituted following onset of acute renal failure and oliguria. Ongoing hemodynamic (Norepinephrine and Milrinone infusion) and respiratory (ventilator) support in the ICU was provided until resolution of intravascular fluid extravasation. Conclusions . SCLS is an extremely rare disorder characterized by unexplained episodic capillary hyperpermeability, which causes shift of volume and protein from the intravascular space to the interstitial space. Patients present with significant hypotension, hemoconcentration, hypovolemia, and oliguria. Severe edema results from leakage of fluid and proteins into tissue. The most important part of treatment is maintaining stable hemodynamics, ruling out other causes of shock and diligent monitoring for complications. Awareness of the clinical syndrome with the rare complication of compartment syndrome may help guide investigations and diagnoses of these critically ill patients.